Search for signatures of magnetically-induced alignment in the arrival directions measured by the Pierre Auger Observatory - Dova, María Teresa (2012)
We present the results of an analysis of data recorded at the Pierre Auger Observatory in which we search for groups of directionally-aligned events (or ‘multiplets’) which exhibit a correlation between arrival direc- tion and the inverse of the energy. These signatures are expected from sets of events coming from the same source after having been deflected by intervening coherent magnetic fields. The observation of several events from the same source would open the possibility to accurately reconstruct the position of the source and also measure the integral of the component of the magnetic field orthogonal to the trajectory of the cos- mic rays. We describe the largest multiplets found and compute the probability that they appeared by chance from an isotropic distribution. We find no statistically significant evidence for the presence of mul- tiplets arising from magnetic deflections in the present data.